Education Quality Management in the Modern School: Approaches in the Context of Continuing Education - Bondar , T. (New Collegium, 2021)
The article is devoted to the study of the quality management system of education in a modern school. In researching this direction, the author relies on the main characteristics of the quality that education must correspond to. Attention is focused on what should be the criteria in solving the problem of education quality. It is concluded that the teacher today has lost the role of a person transferring knowledge, who acts by authoritarian or totalitarian methods, trying to give as much factual information as possible. A teacher today is a mentor who guides and organises educational and upbringing work with students at school. Consequently, the quality of education is aimed at meeting the public demand for the formation of a personality that is ready to actively respond to permanent changes in the social environment and the challenges that education faces today.